Differences in some skills of emotional expression for simple mentally retardation pupils who are integrated and those who are nonintegrated in Hama (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims at recognizing the differences in some skills of emotional expression from teachers’ and parents’ perspectives between the simple mentally retardation pupils integrated in first stage in basic learning and those who are nonintegrated.The population consisted of 20 pupils of simple mentally retardation (8-12 years) integrated in public schools in first stage in basic learning, and 20 peer pupils in private centers. Whereas the teachers were selected (15 male/female) in public schools and (10 male/female) in private centers. Parents (80 )are the fathers and mothers of (20) pupils in public schools and (20) pupils in private centers.The study used the descriptive approach by designing a questionnaire to measure the differences in some skills of emotional expression between the simple mentally retardation pupils who are integrated in public schools and nonintegrated pupils who are in private centers. This questionnaire was distributed to teachers and parents. Then the data were analyzed statistically by SPSS. The results were as follows:-   There are statistically significant differences between integrated and nonintegrated pupils on all dimensions of the scale for the sake of integrated pupils.-   There are statistically significant differences between the means of some skills of emotional expressions (joy, love) according to the variable of gender for the sake of females.-   There are statistically significant differences in (anger)for the sake of males.